The Dynamics Surface Adsorption of Fe Oxide-Humic Substance Complexes - FAHMI, ARIFIN (Jurnal Sumberdaya Lahan, 2011)
Iron (Fe) oxide is the most abundant metallic oxides in the soils, it is highly reactive so that it has a huge influence on the dynamics of chemical balance in the soil both in terms soil fertility and environmental decontamination from toxic metal. Naturally, the surface of Fe oxide is coated with organic substances in the form of complexes compound, this condition may influence on its reactivity and retention capacity to ions in the soil solution. The presence of humic substances may increase or decrease the adsorption capacity of Fe oxide in which the complexes adsorption capacity is highly dependent on some environmental factors. Complexes formation of Fe oxide â humic substances increase cation adsorption esspecially in very acid condition. Ionic strength tends to influence on cation adsorption only at basic pH condition and the increasing of ionic strength is increased cation adsorption by complexes. Adsoption processes is also influenced by concentration, molecule weight dan type of adsorbent and adsorbate material. The presence of competition between ions and blocking process on adsorption process decreases a number of sorbed ion.